High Througput Multicore Server Dengan Kernel Bypass - dimas febriyan priambodo (STMIK Sinar Nusantara, 2020)
Kernel performs one part of the overall operating system utility as a bridge between the user and the hardware. In multi core hardware, the kernel was also created with a general approach so it needs to be adjusted for specific purposes. Kernels for servers using common Kernels have many limitations, such as single socket descriptor, single IRQ, and lack of pooling so that they require some modification to run optimally. Kernel bypass is a method by eliminating the automation of a server used to realize a server, namely high throughput. Kernel bypass is a combination of techniques, modification at the driver level with hashing rx signal and modification of multiple receivers with multiple ip receivers, multiple thread receivers, and multiple port listeners. This combined modification makes the server more reliable with an average throughput increase of 250.44%.